Direct growth of nanocrystalline hexagonal boron nitride films on dielectric substrates - Tay, Roland Yingjie (2015)
Atomically thin hexagonal-boron nitride (h-BN) films are primarily synthesized through chemical vapor deposition (CVD) on various catalytic transition metal substrates. In this work, a single-step metal-catalyst-free approach to obtain few- to multi-layer nanocrystalline h-BN (NCBN) directly on amorphous SiO2/Si and quartz substrates is demonstrated. The as-grown thin films are continuous and smooth with no observable pinholes or wrinkles across the entire deposited substrate as inspected using optical and atomic force microscopy. The starting layers of NCBN orient itself parallel to the substrate, initiating the growth of the textured thin film. Formation of NCBN is due to the random and uncontrolled nucleation of h-BN on the dielectric substrate surface with no epitaxial relation, unlike on metal surfaces. The crystallite size is ∼25 nm as determined by Raman spectroscopy. Transmission electron microscopy shows that the NCBN formed sheets of multi-stacked layers with controllable thickness from ∼2 to 25 nm. The absence of transfer process in this technique avoids any additional degradation, such as wrinkles, tears or folding and residues on the film which are detrimental to device performance. This work provides a wider perspective of CVD-grown h-BN and presents a viable route towards large-scale manufacturing of h-BN substrates and for coating applications.